Cross-border competition : implications for Sri Lanka : case studies of pharmaceutical, cement markets, and shipping lines sector - Knight-John, Malathy; Institute of Policy Studies (Colombo, Sri Lanka); Law and Society Trust (Sri Lanka); Consumer Unity & Trust Society (Colombo : Institute of Policy Studies, 2003)
Collaborative report by Institute of Policy Studies, Law and Society Trust and Consumer Unity & Trust Society on competition in pharmaceutical industry, cement industries, and shipping in Sri Lanka.
Keywords: Competition -- Sri Lanka; Pharmaceutical industry -- Sri Lanka; Cement industries -- Sri Lanka; Shipping -- Sri Lanka